Design of current sources for load common mode optimization - Sirtoli Vinicius G; Morcelles Kaue F; Vincence Volney C (Journal of Electrical Bioimpedance, 2018)
Bioimpedance measurement systems often use the Howland current sources to excite the biological material under study. Usually, difference or instrumentation amplifiers are used to measure the resulting voltage drop on this material. In these circuits, common mode voltage appears as artifacts in the measurement. Most researches on current sources are focused on improving the output impedance, letting other characteristics aside. In this paper, it is made a brief review on the load common mode voltage and output swing of various topologies of Howland current sources. Three circuits are proposed to reduce load common mode voltage and enhance load capability by using a fully differential amplifier as active component. These circuits are equated, simulated and implemented. The three proposed circuits were able to deliver an output current with cut-off frequency (-3dB) higher than 1 MHz for loads as big as 4.7 kΩ. The worst measured load common mode voltage was smaller than 24 mV for one of the circuits and smaller than 8 mV for the other two. Consequently, it could be obtained increases in the Common Mode Rejection Ratio (CMRR) up to 60 dB when compared to the Enhanced Howland Current Source (EHCS).